A carnavalização no contexto escolar: reflexões e refrações suscitadas a partir da aplicação do plano de trabalho docente - Paes, Francisco Cleyton de Oliveira (2024)
This research aims to analyze the effects of meanings provoked by the reflections and refractions of 2nd year high school students, prompted by the Teaching Work Plan, in favor of the development of subjects with a carnivalized posture, taking into account the notion of carnivalization, coined by Bakhtin. To this end, we applied the Teaching Work Plan (PTD) as an instrument for building and developing students' learning in order to improve their literacy. In addition to the set of activities applied, at the end we asked them to produce a carnivalized meme. The corpus of analysis in this thesis is made up of the answers given in the Plan's activities, the production of the memes and a self-assessment made by the students about their learning process. With regard to the theoretical framework and to support the analysis of the data generated, we used the notion of carnivalization (Bakhtin, 1996; 2010); we also tried to understand how laughter works in society and, for this, we used Bakhtin (1996, 2010), Minois (2003) and Terry Eagleton (2020); in addition, we used some notions from Dialogical Discourse Theory: concrete utterance, genres of discourse, axiology and responsiveness (Bakhtin, 2016; Volóchinov, 2017). Finally, we also adopted the perspective of Multiliteracies (Rojo; Moura, 2019; Rojo; Barbosa, 2015). Throughout the development of the PTD, we noticed that the students were improving their critical-reflective thinking, to the point where they were able to analyse the sketches with humorous and carnivalized content and were also able to mobilize carnivalized language in the production of the memes they constructed. Therefore, as the subjects improved their literacy skills as a result of their experience in the classes, we noticed a change in attitude as a result of this transformation.